A Review of Medical Thoracoscopy and Its Role in Management of Malignant Pleural Effusion - Michael Gioia; Rosa L. Arancibia (MDPI AG, 2024)
Pleural effusion is the most common disease among all pleural diseases and affects 1.5 million patients per year in the United States. Different interventions can be performed when dealing with pleural effusions. In this review, we present medical thoracoscopy as a minimally invasive procedure with both diagnostic and therapeutic utility in the management of pleural disease. It has a higher diagnostic yield than commonly performed percutaneous procedures (thoracentesis, closed pleural biopsy) and simultaneously offers many of the therapeutic benefits of more invasive procedures, such as video-assisted thoracoscopic surgery, with a lower risk profile. The role of medical thoracoscopy is evolving and will likely continue to expand as more centers start performing the procedure nationwide.